The Development of Geometry recreation in the form of Math Maze and Learning Equipment Circle Subject on 8th Grade Junior High School - Waluyo, Eko (Department of Mathematics Education , University of Jember, 2024)
The aim of this research is to develop recreational geometry in the form of Math Maze and learning tools for Circle material. The development model used is the Plomp Development Model. The test subjects were Class VIII students at Argopuro Panti Middle School, Jember, academic year 2023/2024. The product developed obtained an average validation score of 3.24 and was included in the valid category, student activity was obtained on average 93.5% which was included in the very active category and from the student response questionnaire, it was obtained that 98% of students were very happy with learning-based learning. recreational geometry in the form of Math Maze. It can be said that the product developed is valid and practical Key words: recreational geometry, circles, teaching modules, LKPD